Statement for Parliament made by H.E. Carl B. Greenidge, Vice President and Minister of Foreign Affairs at the opening of 11th Parliament of the National Assembly and address at the opening of the Forum on the Genesis of Territorial Issues and the Evolution of Frontiers Policy ([Ministry of Foreign Affairs] GeorgetownGY, 2015)
Presents a synopsis of the Guyana-Venezuela boundary dispute.
Keywords: BOUNDARIES